Primary care for people with Parkinson's disease in Brazil: A referral flowchart based on risk of falls - Myra, Rafaela Simon; Koerich, Micheline Henrique Araújo da Luz; Gregório, Elaine Cristina; Swarowsky, Alessandra (Frontiers in Public Health, 2022)
Background: People with Parkinson's disease need to exercise to have a better quality of life. The risk of falling needs to be considered when choosing and implementing exercise interventions. Flowcharts are used to facilitate referrals in the Brazilian primary care network, but there is no specific one for Parkinson's disease. Aim: To develop a referral flowchart for people with PD in Brazilian primary care based on the risk of falls and scientific evidence in the context of a multidisciplinary approach. Methods: The development of the referral flowchart was accomplished in three steps; 1) relevant literature was reviewed 2) semi-structured interviews (in focus groups) were conducted with primary health care professionals to investigate the current care for people with Parkinson's disease, and 3) the information obtained from the previous steps were analyzed to inform the development of the referral flowchart. Results: The fall risk-based flowchart uses the 3-step-fall-prediction tool. The primary health care professional should refer the person with a low risk of falls to activities with minimal supervision and those with a higher risk of falls to specialized neurology services. Neurology services are also the referral target for persons presenting significant mobility restrictions (i.e. restricted to a wheelchair or bed). The referral occurs according to what is available in Brazilian primary care. Conclusion: This flowchart might be the first step to build a multidisciplinary approach for people with Parkinson's disease in Brazilian primary care. The next stage of this study is the validation and subsequent implementation of the flowchart through the primary care at Unified Health System in Brazil.